2021
DOI: 10.1186/s42523-021-00141-0
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling differences in fecal microbiota stability in mammals: from high variable carnivores and consistently stable herbivores

Abstract: Background Through the rapid development in DNA sequencing methods and tools, microbiome studies on a various number of species were performed during the last decade. This advance makes it possible to analyze hundreds of samples from different species at the same time in order to obtain a general overview of the microbiota. However, there is still uncertainty on the variability of the microbiota of different animal orders and on whether certain bacteria within a species are subject to greater f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 84 publications
5
29
0
Order By: Relevance
“…The presence of other bacterial genera reported in this study could be the result of environmental and genetic factors, age, breed, diet, phylogeny, among others (56,57,58) . Recently (56,59,60) , was demonstrated that herbivorous animals have the most diverse microbiota since they depend on microbial metabolic pathways to maximize energy and nutrient extraction from feeding (61) . Although the gut microbiome usually remains stable over time assisting as a system against pathogens and other disease-causing agents in the host, the disturbance of this community can lead to animal disease (62,63) .…”
Section: Resultsmentioning
confidence: 99%
“…The presence of other bacterial genera reported in this study could be the result of environmental and genetic factors, age, breed, diet, phylogeny, among others (56,57,58) . Recently (56,59,60) , was demonstrated that herbivorous animals have the most diverse microbiota since they depend on microbial metabolic pathways to maximize energy and nutrient extraction from feeding (61) . Although the gut microbiome usually remains stable over time assisting as a system against pathogens and other disease-causing agents in the host, the disturbance of this community can lead to animal disease (62,63) .…”
Section: Resultsmentioning
confidence: 99%
“…However, researchers should consider the taxon and study system of interest when developing research projects as taxon-specific factors might impact study outcomes. For example, Zoelzer et al (2021) show that fecal microbiome diversity is significantly higher in herbivores than in carnivores, whereas intraspecific microbiome variation is high in carnivores but not in herbivores. Considering taxon-specific factors (e.g., diet and ecological context of the environment in which organisms occur) can therefore help ensure the success of research initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this workflow makes it possible to analyse several samples at the same time in order to obtain a general overview of the microbiota, which could be useful for routine surveillance and early detection of foodborne pathogens [ 36 ]. Beyond that, as the microbiota influences various physiological and behavioural processes, a healthy microbiota would be correlated with an animal’s fitness, making it possible to identify health and welfare deviations in the animals [ 71 ]. Though the workflow proposed here was based on data analysed after complete data collection, taxonomy sequences were obtained a posteriori, after the sequencing process finished, using per-sequence timestamps added by the nanopore sequencing system itself to each read.…”
Section: Discussionmentioning
confidence: 99%